A Bitter Taste in Your Heart - Bloxham, Conor J.; Foster, Simon R.; Thomas, Walter G. (Frontiers in Physiology, 2020)
The human genome contains 29 bitter taste receptors (T2Rs), which are responsible for detecting thousands of bitter ligands, including toxic and aversive compounds. This sentinel function varies between individuals and is underpinned by naturally-occurring T2R polymorphisms, which have also been associated with disease. Recent studies have reported the expression of T2Rs and their downstream signaling components within non-gustatory tissues, including the heart. Though the precise role of T2Rs in the heart remains unclear, evidence points towards a role in cardiac contractility and overall vascular tone. In this review, we summarize the extra-oral expression of T2Rs, focusing on evidence for expression in heart; we speculate on the range of potential ligands that may activate them; we define the possible signaling pathways they activate; and we argue that their discovery in heart predicts an, as yet, unappreciated cardiac physiology.